Mechanism of welding system technology of automation processes based on artificial intelligence (Eurasian Journal of Engineering and Technology, 2024)
In technological processes, welding systems are being changed by the emergence of modern information technologies such as the Internet and things, big data, artificial intelligence, cloud computing and intelligent manufacturing systems are developing widely. Smart welding systems using these technologies are attracting attention from the academic and industrial communities. Intelligent welding is the use of computers to imitate, augment and/or replace human operators in sensing, learning, decision-making, monitoring and control, etc. This is achieved by combining the advantages of human and physical systems into intelligent cyber systems. Smart welding finds and provides a systematic analysis of experimental applications in the industry, its components, applications and future directions, helping to provide a unified definition of smart welding systems. This article explores the key components and techniques needed to make welding systems intelligent, including sensing and signal processing mining and selection, modeling, decision making, and learning. Emerging technologies and their application to IWS capabilities are also explored, including Industry, cyber-physical systems, digital twins, and more. Typical applications such as welding design, task sequencing, robot path planning, robots are studied. programming, process monitoring and diagnostics, forecasting, process control, quality inspection and evaluation; humanrobot collaboration and virtual welding. Finally, conclusions and suggestions for future development are offered. This review is designed to provide an up-to-date reference for those interested in implementing smart welding capabilities in traditional welding stations, looking at plant process modernization and systems studies